A statistical model for cardiovascular response to exercise - Parazo, Mercedita A.
The aims of this paper is to find a statistical model that will best describe the response of different groups of people to exercise, the equation for determining the maximum response of groups of people, to determine formulas that will best compare the responses of the different groups of individuals.
Thesis (MS Public Health, Biometry)--University of the Philippines Manila, 1979
Keywords: Exercise testing; Treadmill exercise tests